Radiographic evaluation of lesion sizes of histologically diagnosed periapical cysts and granulomas - Zain, R.B.; Roswati, N.; Ismail, K. (1989)
A total of 149 periapical lesions were classified histologically into cysts, granulomas and other lesions. It was found that 53 were cysts, 39 were granulomas and 8 were other lesions. Of the 149 periapical lesions classified, 69 selected cases of cysts and granulomas were obtained and radiographic measurements of area (mm2), largest diameter (mm) and largest root-to-border distance (mm) were recorded. It was found that there is an apparent increase in cystic prevalence with an increase in the area, largest diameter or largest length of the periapical lesions radiographically. A cystic prevalence of 92-100 is observed with a radiographic area of greater than 200 mm2, a radiographic distance and diameter of greater than 20 mm.